Nas entrelinhas da imagem: a Sociologia, o Cinema, o Amor e a Nudez nos filmes Magic Mike e Showgirls - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
This master's research in Sociology is called “Between the lines of the image. Sociology, cinema, love and nudity in the movies Magic Mike and Showgirls”. It aims to analyze how cinematographic conventions aligned with moral, gender and sexual relations are reproduced in current cinema, having as research field the films Magic Mike (2012) and Showgirls (1996). Therefore, the methodology used in this research consisted of the selection of two films, the observation of what was different and repeated in these films, the analysis of the lines between the characters and the use of images and dialogues throughout the dissertation. In addition, different authors and authors were used to help understand the themes selected in this research, such as Heinich (2008) and Le Breton (2012) on sociology of art and sociology of the body, Carrière (2015) and Louro (2008) on cinematographic language and sexuality in cinema, Alcântara (2013) and Rossi (2013) on love in cinema, as well as Keesey & Ducan (2005) and Paley (2001) on nudity in cinema, among others.As a result of this research, it was found that the origin of cinema and its transformations as a specific art (cutting, editing and cinematographic language) brought social norms (morals, gender and sexuality, mainly with the implementation of the Hays code) to making a film, which even today, to a greater or lesser degree, influences the way of making cinema (specifically Hollywoodin this research) as analyzed in the love relationships of the movie Magic Mike, which contrasts thecharacters' quest for sexual pleasure versus the quest implicit by romance and marriage, in other words, in the way female nudity is explicit in Showgirls versus the concealment of male nudity in Magic Mike, showing how these social norms still influence cinema today.
Keywords: Nudez no cinema; Amor no cinema; Arte e cinema; CIENCIAS HUMANAS; Sociologia; Cinema; Nudez; Amor